IOT Based Automatic Light Control System Using MQTT Protocol - Sima, Brema Arisma; Buaton, Relita; Sihombing, Marto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
An Internet of Thing-based automatic light control system using the MQTT protocol is an efficient solution for controlling lights on or off. This study aims to design and implement an IOT-based automatic light control system that can be accessed and controlled via the internet network. This system uses the MQTT protocol to communicate between the hardware and software connected to the MQTT Broker. This system also consists of several main components, namely a light sensor, NodeMCU ESP8266, and a user application. The light sensor is used to detect the intensity of surrounding light, NodeMCU ESP8266 to connect to Wi-Fi networks and broker MQTT. The MQTT broker serves as a communication center between publishers and subscribers. MQTT Dash is a user application that provides an interface for manually controlling the user's lights or setting the automatic mode.